The Impact of Yes-Associated Protein 1 (YAP1) Expression Patterns in Locally Advanced Breast Cancer: Associations with Pathological Response and Tumor Features - Osman Erinc; Sabin Goktas Aydin; Taskin Erkinuresin; Ozgur Yilmaz; Ahmet Aydin; Sevinc Dagistanli; Murat Akarsu (Medicina)
Background and Objectives: The Hippo pathway, via Yes-associated protein 1 (YAP1), regulates cell proliferation, apoptosis, and tissue regeneration. Aberrant YAP1 activation is linked to tumor progression and immune evasion in various cancers, including breast carcinoma, despite conflicting evidence on its prognostic value. Preclinical studies have explored drugs targeting YAP1–TEAD interactions, but therapeutic application is limited. Materials and Methods: This study included 50 patients with locally advanced breast cancer, who were assessed by a multidisciplinary tumor board and underwent neoadjuvant treatment per tumor subtype and clinical guidelines. Eligibility required both pre-treatment core biopsy and post-treatment surgical resection samples. Due to the absence of residual tumor in some patients achieving complete pathological response, post-treatment tissue was available and analyzable in 30 patients. YAP1 expression was evaluated immunohistochemically for nuclear and cytoplasmic staining patterns. ROC analysis identified a cutoff for YAP1 expression, defining tumors with ≥70% nuclear and ≥80% cytoplasmic staining. Results: YAP1 expression had a significant relationship with tumor subtype (p = 0.001), being most frequent in HER-2-positive tumors (55.6%) and least frequent in luminal tumors (11.1%). YAP1 positivity significantly predicted axillary pathological complete response (pCR) (p = 0.01). In YAP1-positive patients, 77.8% achieved axillary pCR compared to 31.7% in YAP1-negative patients, though the YAP1 status and breast pCR association were insignificant (p = 0.07). The Mann–Whitney U test indicated that higher Ki-67 values were significantly associated with positive YAP1 expression (p = 0.028). In contrast, there was no association between ER, PR status, age, and tumor size. Following treatment, there was a statistically significant change in YAP1 expression, with nuclear staining decreasing (p = 0.004) while cytoplasmic staining increased (p = 0.002). YAP1 was significantly linked to axillary pCR, HER-2 status, and Ki-67. Conclusions: Post treatment, nuclear YAP1 decreased, whereas cytoplasmic expression increased, showing a localization shift. These results suggest that YAP1 may predict treatment response and become a future therapeutic target.